EXPERIMENTAL STUDY IMPROVEMENT OF QUALITY OF HOE ON SMALL METAL INDUSTRY IN THE DISTRIC PRINGSEWU - Hamni, Arinal (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2014)
Considering the extent of agriculturalland Pringsewu District, then surely it takes quality agricultural equipment that can launch the agricultural activities in the region. Hoe is one of agricultural equipment that need to be upgraded. Previously been conducted making a hoe by Small Metal Industries in District Pringsewu cooperation with the Ministry of Industry by adjusting the conditions of the local ordinary farmland gardening, but the result have not been up in terms of both size and hardness values. Research in improving the quality of hoe is done to get the size and hardness values that follow the standard SNI 02-0331-1989. Materials used in this study was AISI 1020 steel. In order to fit a standard hoe, then made modifications to the dimensions of hoe, and to increase its hardness value according to the standard, pack carburizing method is used with a cheap media there are Albizia wood charcoal, palm shell waste, and low rank coal. The result of research have shown that after the modification in size, the hoe has been able to comply SNI standard while maintaining the curvature of the hoe in order to guarantee a splash of water disturbance at the time of digging remained insurmountable. Then the value of hardness standard hoe KW III was achieved at 39 HRC, obtained from the hoe to use the media pack carburizing Albizia wood charcoal Keywords : hoe, quality improvement, AISI 1020, pack carburizing, SNI